ANALISIS KESIAPAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM PENERAPAN PEMBELAJARAN TATAP MUKA TERBATAS (PTMT) DI MASA NEW NORMAL - Amirul Hayat (ANDRAGOGI, 2022)
This study aims to analyze the readiness of Islamic Religious Education (PAI) teachers in the application of Limited Face-to-face Learning (PTMT) in the new normal period. This type of research is a quantitative descriptive study with a survey method. The subjects in this study were PAI teachers at all state high schools in Muara Enim Regency, which consisted of 46 teachers. Data collection techniques used in this study were questionnaires and documentation. The collected data will be analyzed by data analysis stages consisting of data coding (data coding), data transfer to a computer (data entering), data cleaning (data cleaning), data presentation (data output), and data analysis (data analyzing). The results obtained after carrying out the research are PAI teachers who teach at public high schools throughout Muara Enim Regency are categorized as mostly ready to carry out limited face-to-face learning (PTMT) during the New Normal period. This is based on the results of the percentage of work readiness for each: 1) Safety and Health 96.7%; 2) Responsibility 93.5%; 3) Communication 93.5%; 4) Skills 92.7; 5) Flexibility 87%; and 6) Self View 87.2%. In carrying out learning the teacher still pays attention to safety and health by implementing health protocols. In addition, the delivery of material carried out by teachers in PTMT learning should use effective language so that communication runs smoothly so that the material can be conveyed well with students.Keywords: PAI teacher readiness, limited face-to-face learning, the new normal era Abstrak Penelitian ini bertujuan untuk menganalisis kesiapan guru Pendidikan Agama Islam (PAI) dalam penerapan Pembelajaran Tatap Muka Terbatas (PTMT) pada masa new normal. Jenis penelitian ini adalah penelitian deskriptif kuantitatif dengan metode survei. Subjek dalam penelitian ini adalah guru PAI di seluruh SMA Negeri di Kabupaten Muara Enim yang terdiri dari 46 guru. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah angket dan dokumentasi. Data yang terkumpul akan dianalisis dengan tahapan analisis data yang terdiri dari pengkodean data (data coding), transfer data ke komputer (penginputan data), pembersihan data (data cleaning), penyajian data (data output), dan analisis data (data analysis). . Hasil yang diperoleh setelah melakukan penelitian adalah guru PAI yang mengajar di SMA Negeri se Kabupaten Muara Enim sebagian besar dikategorikan siap melaksanakan pembelajaran tatap muka terbatas (PTMT) pada masa New Normal. Hal ini berdasarkan hasil persentase kesiapan kerja untuk masing-masing: 1) Keselamatan dan Kesehatan Kerja 96,7%; 2) Tanggung jawab 93,5%; 3) Komunikasi 93,5%; 4) Keterampilan 92,7; 5) Fleksibilitas 87%; dan 6) Pandangan Diri 87,2%. Dalam melaksanakan pembelajaran guru tetap memperhatikan keselamatan dan kesehatan kerja dengan menerapkan protokol kesehatan. Selain itu penyampaian materi yang dilakukan oleh guru dalam pembelajaran PTMT hendaknya menggunakan bahasa yang efektif agar komunikasi berjalan lancar sehingga materi dapat tersampaikan dengan baik kepada siswa.Kata Kunci: Kesiapan guru PAI, pembelajaran tatap muka terbatas, era new normal